Optimizing Hot Embossing of Poly(methyl methacrylate) Microfluidic Chip - Whulanza, Yudan; Dhira, Pandya; Haryadi, Deni; Soemardi, Tresna P. (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Microfluidic research become a more important research field in mechanical and bioengineering fields. The application of microfluidic positively relates to the ability to manufacture micro or precision. Nowadays, the manufacturing in this area is aimed at around 100-500 µm. Here, a hot embossing method is reported to realize microchannel with height and width dimensions of 150-300 µm and 600-800 µm, respectively. This study also shows that the margin factor between the mould/dies to the realized dimension is 50-70% and 5-7% for height and width, respectively.